(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Print media is one of several media types including newspapers, magazines, books, and so on. Electronic and online media are also included in the communication media, which functions as an intermediary in disseminating information. One of the functions of the internet is to disseminate information digitally or online that can be accessed by anyone, anywhere and anytime, while connected to the network. Communication media is a means of connecting that can help disseminate this information. Fast, precise, and accurate information is needed in various institutions and companies in the current era of globalization. This community service activity aims as a forum for information to institutional administrators and the Baubau City community, then as a place to report activities by IMM Baubau City, then the goal is to be used as a means of branding and marketing IMM Baubau City Branch to prospective members or sympathisers to be easily attracted to the management or activities of IMM Baubau City. The results of this socialization and training activity can provide solutions for leaders and commissariats to make the immbaubau.or.id website a centralized and trusted source of information. Once achieved, this will [insert benefits here] and can make the website an online archive that can be uploaded and downloaded anytime and anywhere.